Tracing Agricultural Land Transfer in China: Some Legal and Policy Issues - Chao Zhou; Yunjuan Liang; Anthony Fuller (Land, 2021)
This paper traces the evolution of land tenure changes in contemporary China since 1949. The transfer of land from peasant households to family farms and commercial sized units is on a vast scale and forms one of the greatest land reforms we have ever seen. The agrarian question forms both the policy and academic context in which this legislative account of land transfer is assessed and raises the question of whether land assembly in China resembles previous agricultural transformation policy and processes in industrialized countries or to what extent it has special characteristics of its own. The security of land holding in rural China, established with the household responsibility system, is seen to mature slowly over three to four periods of adjustment, always protecting the rights of peasants while improving conditions for increasing land productivity, resulting in an extension of the two rights of peasant holdings to three rights in the new millennium. The introduction of a third right, a land management right which is transferable from peasants to outsiders, has enabled a huge land assembly movement affecting millions of small holdings. This process of land tenure restructuring raises such questions as the consequences of the capitalization of agriculture, peasant land dispossession, proletarianization, and the prospect of a future land market in rural China, all topics for further research.